Rainbow Seen from 3506 E. Balch Avenue, Fresno - Watkins, Howard::::::::: (1988)
Robin Watkins pointing to the rainbow in sky Wearing pink and white striped dress with flowers made by her grandmother Francis Kamp; casting 50 foot shadow